USE OF WEB RADIO IN INTEGRATED HIGH SCHOOL: A DIALOGUE ANCHORED IN FREIRIANA’S CONCEPTIONS - José de Magalhães Lima, Jaime; Gilberto Mendes dos Santos, Francisco; Horn Rodrigues, Raulina (Revista Gênero e Interdisciplinaridade, 2022)
The article presents radio in the school environment, as a didactic resource to promote the teaching-learning process, reporting the experience of the Extension Project “Communicating and integrating is necessary: Rádio integraIF”. The Project was developed between February and November 2019 and was aimed at integrated high school students. Its objective was to meet the information, integration and entertainment needs of high school students at the Instituto Federal do Acre, Campus Tarauacá-Acre. The proposal focused on five stages: a) Presentation of the project and raising awareness among students; b) Training workshops; c) Organization of the physical structure; d) Planning and execution of schedules; and, e) Assessment, through a conversation circle. In the end, it was verified that the project contributes to improve coexistence and group work, respect for differences, and the levels and rhythms of learning of each of the team members, in addition to stimulating oral communication, a sense of responsibility, autonomy, the capacity for initiative, can still favor interdisciplinarity, social interaction and entertainment.